2016
DOI: 10.2147/prbm.s119275
|View full text |Cite
|
Sign up to set email alerts
|

Internet use and addiction among medical students of Universiti Sultan Zainal Abidin, Malaysia

Abstract: BackgroundThe use of Internet has now become indispensable, and the technology has revolutionized the medical education and practice worldwide. Currently, medical students and professionals have an enormous opportunity to keep them always updated with the exponential growth of knowledge because of potential progression of Internet throughout the world that enables them to become a lifelong learner. Internet addiction is a widespread phenomenon among students and academicians at universities in Malaysia. Studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
34
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 43 publications
(55 reference statements)
9
34
5
1
Order By: Relevance
“…They were no statistically significant differences between genders. Both male and female were equally addicted to smartphones which are supported by other findings from recent studies [8,17,18] although according to a research done among the students of a medical university in South India, males were twice more addicted to smartphones [7] while other studies revealed the opposite [19].…”
Section: Discussionsupporting
confidence: 65%
“…They were no statistically significant differences between genders. Both male and female were equally addicted to smartphones which are supported by other findings from recent studies [8,17,18] although according to a research done among the students of a medical university in South India, males were twice more addicted to smartphones [7] while other studies revealed the opposite [19].…”
Section: Discussionsupporting
confidence: 65%
“…This rate is relatively higher compared to the study finding conducted among university student in another university in Malaysia which was in 32%. 22 In another study among undergraduate students in Nigeria, 30% of the study sample were found to have problematic internet use. 23 It must be noted that comparing these studies is difficult because of differences in social and cultural contexts.…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of problematic internet use (PIU) was greater among university students. For instance, the prevalence was 36.9 to 81% in Malaysian medical students (21,22) (26). Internet addiction among university students in Ethiopia has not been studied.…”
Section: Introductionmentioning
confidence: 99%